Endoscopic considerations for the management of cholangiocarcinoma. Issue 3 (5th November 2021) - Geraghty, Joe
Abstract: Cholangiocarcinoma (CCA) is a rare malignancy of the biliary tract. The goals of endoscopy in CCA are to (a) provide an accurate diagnosis (tissue acquisition) and staging of disease and (b) relieve biliary obstruction and associated symptoms such as pruritis (stent placement). This then facilitates optimal treatment to occur; be this surgical resection, uninterrupted chemotherapy or improvement in symptoms. Endoscopy can involve endoscopic retrograde cholangiopancreatography with or without cholangioscopy, or endoscopic ultrasound with fine‐needle aspiration to support these goals of making surgery safer and chemotherapy possible while avoiding endoscopy compilations such as pancreatitis and sepsis.